Simulation-based framework to evaluate resistivity of cooling strategies in buildings against overheating impact of climate change. (15th January 2022) - Rahif, R.; Hamdy, M.; Homaei, S.; Zhang, C.; Holzer, P.; Attia, S.
Abstract: Over the last decades overheating in buildings has become a major concern. The situation is expected to worsen due to the current rate of climate change. Many efforts have been made to evaluate the future thermal performance of buildings and cooling technologies. In this paper, the term "climate change overheating resistivity" of cooling strategies is defined, and the calculation method is provided. A comprehensive simulation-based framework is then introduced, enabling the evaluation of a wide range of active and passive cooling strategies. The framework is based on the Indoor Overheating Degree (IOD), Ambient Warmness Degree (AWD), and Climate Change Overheating Resistivity (CCOR) as principal indicators allowing a multi-zonal approach in the quantification of indoor overheating risk and resistivity to climate change. To test the proposed framework, two air-based cooling strategies including a Variable Refrigerant Flow (VRF) unit coupled with a Dedicated Outdoor Air System (DOAS) (C01) and a Variable Air Volume (VAV) system (C02) are compared in six different locations/climates. The case study is a shoe box model representing a double-zone office building. In general, the C01 shows higher CCOR values between 2.04 and 19.16 than the C02 in different locations. Therefore, the C01 shows superior resistivity to the overheating impact of climate change compared to C02. The maximum CCOR value of 37.46 is resulted for the C01 in Brussels, representing the most resistant case, whereas the minimum CCOR value of 9.24 is achieved for the C02 in Toronto, representing the least resistant case. Highlights: The framework is comprehensive enabling universal comparative analysis. IOD, AWD, and CCOR are used as principal performance indicators. The methodology is tested by comparing VRF with DOAS and VAV.